2011
DOI: 10.1007/s00436-011-2636-5
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium spp. parasitize exotic birds that are commercialized in markets, commercial aviaries, and pet shops

Abstract: The purpose of this study was to genetically characterize and phylogenetically analyze the Cryptosporidium spp. isolated from exotic birds commercialized in popular markets, commercial aviaries, and pet shops located in Rio de Janeiro, Brazil. Fecal samples from individually housed birds were collected and subjected to centrifuge-flotation technique using saturated sugar solution. DNA was isolated from Cryptosporidium positive samples, and 18S subunit rDNA was amplified and processed using nested-polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…In addition to C. meleagridis , other zoonotic species of Cryptosporidium reported in birds include C. hominis , C. parvum , C muris and C. andersoni (Zylan et al., 2008, Jellison et al., 2009, Ryan, 2010, Reboredo-Fernández et al., 2015, Gomes et al., 2012). In addition, twelve genotypes; avian genotypes I–V, the black duck genotype, the Eurasian woodcock genotype and goose genotypes I–V have been reported (Table 3).…”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%
“…In addition to C. meleagridis , other zoonotic species of Cryptosporidium reported in birds include C. hominis , C. parvum , C muris and C. andersoni (Zylan et al., 2008, Jellison et al., 2009, Ryan, 2010, Reboredo-Fernández et al., 2015, Gomes et al., 2012). In addition, twelve genotypes; avian genotypes I–V, the black duck genotype, the Eurasian woodcock genotype and goose genotypes I–V have been reported (Table 3).…”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%
“…Avian genotype I has been found in canaries (Serinus canaria) and Indian peafowl (Pavo cristatus) (NG et al, 2006;NAKAMURA et al, 2009), whereas the presence of avian genotype III has been reported in several species of Psittaciformes and Passeriformes (NG et al, 2006;NAKAMURA et al, 2009;MAKINO et al, 2010;QI et al, 2011;GOMES et al, 2012;NAKAMURA et al, 2014).…”
Section: Proventriculusmentioning
confidence: 99%
“…Asia, South America , Qi et al (2011), Nakamura et al (2014) Goose genotypes I-V Anserifornes nd 18S rRNA North America Jellison et al (2004), Zhou et al (2004) Black duck genotype Gomes et al (2012), Reboredo-Fernández et al (2015) Cryptosporidium hominis Anseriformes nd 18S rRNA North America Zhou et al (2004) nd: the site of infection was not reported.…”
Section: Proventriculusmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cryptosporidium species can infect human beings as well as other animals; it is mainly located in the epithelial cells of the gastrointestinal tract, and is likely in the respiratory tract [7], particularly in the case of infection by C. meleagridis , a bird species. The main clinical manifestation is persistent diarrhea, and respiratory disturbances can occasionally be observed [5, 12].…”
Section: Introductionmentioning
confidence: 99%